The Impact of a Dedicated Sedation Team on the Incidence of Complications in Pediatric Procedural Analgosedation - Sofia Apostolidou; Mirna Kintscher; Gerhard Schön; Chinedu Ulrich Ebenebe; Hans-Jürgen Bartz; Dominique Singer; Christian Zöllner; Katharina Röher (MDPI AG, 2022)
The number of pediatric procedural sedations for diagnostic and minor therapeutic procedures performed outside the operating room has increased. Therefore, we established a specialized interdisciplinary team of pediatric anesthesiologists and intensivists (Children's Analgosedation Team, CAST) at our tertiary-care university hospital and retrospectively analyzed the first year after implementation of the CAST. Within one year, 784 procedural sedations were performed by the CAST; 12.2% of the patients were infants <1 year, 41.9% of the patients were classified as American Society of Anesthesiologists (ASA) grade III or IV. Most children received propofol (79%) and, for painful procedures, additional esketamine (48%). Adverse events occurred in 51 patients (6.5%), with a lack of professional experience (OR 0.60; 95% CI 0.42-0.81) and increased propofol dosage (OR 1.33; 95% CI 1.17-1.55) being significant predictors. Overall, the CAST enabled safe and effective procedural sedation in children outside the operating room.